Philia as Fellowship in Plato’s Lysis - Payne, Andrew (Revista Archai, 2023)
Socrates in the Lysis discusses philia and the conditions under which two or more people can be said to engage in this relationship. Many commentators take Socrates to be attempting to discover how human beings enter into the relationship of friendship, a relationship characterized by reciprocal affection, altruistic concern and personal intimacy. Other readers of the Lysis see in the dialogue’s investigation of philia a discussion of desire and attraction at the most general level. On this view, philia is one species of the general human desire for good. The present paper develops a third reading of philia. Philia is a type of partnership or fellowship where affection and intimacy are not central features of the relationship. The fellowship involves at least one party who possesses wisdom while other members of the fellowship seek to benefit from wisdom. Thus philia is a characteristically human response to the need for wisdom. The members of such a fellowship share a common desire for a good which gives purpose to their association, and because of their common desire to benefit from this good the members can be described as fellows or partners in the pursuit of this good.